2022
DOI: 10.3390/molecules27155008
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicinal Plants as a Source of Inspiration for Osteosarcoma Therapy

Abstract: Osteosarcoma is one of the most common types of bone cancers among paediatric patients. Despite the advances made in surgery, chemo-, and radiotherapy, the mortality rate of metastatic osteosarcoma remains unchangeably high. The standard drug combination used to treat this bone cancer has remained the same for the last 20 years, and it produces many dangerous side effects. Through history, from ancient to modern times, nature has been a remarkable source of chemical diversity, used to alleviate human disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…Osteosarcoma is a common type of cancer in orthopaedic clinics, and despite ongoing extensive research, no significant therapeutic improvements have been achieved in the last few decades [4]. Earlier findings have suggested that osteosarcoma is a highly variable cancer, both in its clinical presentation and on a cellular and molecular level [22]. Paradoxically, only four drugs, cisplatin, DOX, isocyclophosphamide, and methotrexate, are currently used to treat this cancer, and chemotherapy-induced toxicity remains an unresolved problem in osteosarcoma and other cancers [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is a common type of cancer in orthopaedic clinics, and despite ongoing extensive research, no significant therapeutic improvements have been achieved in the last few decades [4]. Earlier findings have suggested that osteosarcoma is a highly variable cancer, both in its clinical presentation and on a cellular and molecular level [22]. Paradoxically, only four drugs, cisplatin, DOX, isocyclophosphamide, and methotrexate, are currently used to treat this cancer, and chemotherapy-induced toxicity remains an unresolved problem in osteosarcoma and other cancers [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a wide variety of natural products that stimulate autophagy by interfering with the PI3K/AKT/mTOR pathway in OS cells are described in Table 2 [ 106 ].…”
Section: Modulation Of Autophagy In Os Therapeuticsmentioning
confidence: 99%
“…Over half of anticancer drugs contain natural products with phytochemical components that offer antibacterial, anticancer, and neuroprotective effects (Choudhari et al, 2019). When focused speci cally on osteosarcoma, studies documenting the anti-cancer capabilities of plant-derived metabolites reveal a range of processes and pathways involved in creating these effects (Kazantseva et al, 2022). These phytochemicals act on several apoptotic pathways and augment the therapeutic advantages of conventional medications, they are chosen in combination therapy (Rodriguez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%